Examining how integrating digital technology with traditional media impacts the process of Artmaking in the art classroom : a case study of Grade 6 class in an independent girls school in Gauteng - Motake, Siphesihle (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.